2020
DOI: 10.3390/ijerph17176391
|View full text |Cite
|
Sign up to set email alerts
|

Association of Summer Heat Waves and the Probability of Preterm Birth in Minnesota: An Exploration of the Intersection of Race and Education

Abstract: Preterm birth (PTB) is common and has negative impacts on infant health. While some maternal risk factors have been identified, including age under 20 or over 40, substance abuse, low BMI, and racism, less is known about the impact of environmental exposures like high heat. We combined 154,157 records of live births occurring in Minnesota between 2009 and 2015 with hourly weather records collected from the Minneapolis–St. Paul airport. We tested if maternal heat wave exposure (a seven-day period with a mean da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
2
19
0
1
Order By: Relevance
“…We observed that heatwaves were more strongly associated with both early-term and preterm birth among non-Hispanic black and Hispanic mothers. These findings are in-line with those from previous studies [ 31 , 47 , 48 ]. Minority groups might be more vulnerable to heatwave events due to a lack of a cooling system in the household and less access to neighborhood greenness.…”
Section: Discussionsupporting
confidence: 94%
“…We observed that heatwaves were more strongly associated with both early-term and preterm birth among non-Hispanic black and Hispanic mothers. These findings are in-line with those from previous studies [ 31 , 47 , 48 ]. Minority groups might be more vulnerable to heatwave events due to a lack of a cooling system in the household and less access to neighborhood greenness.…”
Section: Discussionsupporting
confidence: 94%
“…Nine studies employed apparent temperature (combined effect of air temperature and relative humidity) to identify the exposure effects on elevated ambient temperatures on pregnant women and neonates [11,12,[32][33][34][35][36][37][38]. Twelve studies examined the effects of heatwaves/extreme heat events on maternal, foetal, and neonatal outcomes [6,32,[38][39][40][41][42][43][44][45][46][47]. They used different heatwave characteristics, i.e., length of exposure, threshold percentile (75th, 90th, 95th, and 98th percentile to identify high temperatures), peak temperature, and a number of heatwaves/heat events, to estimate the magnitude of the exposure effects [6,32,[38][39][40][41][42][43][44][45][46][47].…”
Section: The Magnitude Characteristics and Trends Of Research On Elev...mentioning
confidence: 99%
“…Twelve studies examined the effects of heatwaves/extreme heat events on maternal, foetal, and neonatal outcomes [6,32,[38][39][40][41][42][43][44][45][46][47]. They used different heatwave characteristics, i.e., length of exposure, threshold percentile (75th, 90th, 95th, and 98th percentile to identify high temperatures), peak temperature, and a number of heatwaves/heat events, to estimate the magnitude of the exposure effects [6,32,[38][39][40][41][42][43][44][45][46][47]. No consistent definition for 'heatwave' or 'extreme heat event' was observed among reviewed studies.…”
Section: The Magnitude Characteristics and Trends Of Research On Elev...mentioning
confidence: 99%
See 2 more Smart Citations